Bait - Ryerson, Sean; Fuqua, Antoine ([ Burbank, CA] : Warner Home Video, 2001)
Alvin Dean Sanders doesn't get it. He doesn't know why his conviction for small-time theft is wiped from the record - poof! - just like that. Or why $11,500 in walking-around money is laid on him. Alvin doesn't know he's the bait in a snaky government scheme to capture a killer, thanks to an electronic implant. But he's starting to grow suspicious
Executive producer, Tony Gilroy, Jame Rucker King ; witer, Andrew Scheinman, Adam Scheinman
Cast: Jamie Foxx, David Morse, Doug Hutchinson, Kimberly Elise
Keywords: Comedy films